Max Herrmann og Lessingsyndromet - Risum, Janne (Peripeti, 2021)
In this article I take it upon myself to show that there are good reasons to distinguish between the theatre production as a prepared and structured work of art, and the theatre performance as a transitory presentation of it to spectators; and that there is consequently no reason to presume a general antagonism between the drama as a written work of art and the theatre performance as an event. I do so by primarily discussing the pioneering German theatre scholar Max Herrmann’s (1865-1942) views on both issues, and by also drawing in the views of Aristotle and Lessing. Accordingly I refute Erika Fischer-Lichte’s interpretation of Herrmann’s conception of the theatre performance as entirely corresponding to her own idea of the performative as transitory in her book from 2004, Ästhetik des Performativen (in English The Transformative Power of Performance: A New Aesthetics, 2008).